2022
DOI: 10.1007/s10570-022-04636-0
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of green synthesized silver-decorated magnetic particles for coating of bioactive packaging

Abstract: To avoid bacterial and viral infections on food products, the use of antibacterial and antiviral packaging offers great benefit to the food industry. In this study, the coating of paper packaging with silver-decorated magnetic particles (Ag@Fe 3 O 4 ) was developed. The Ag@Fe 3 O 4 was prepared by a facile and environmentally friendly method using extracted spent coffee grounds (ex-SCG). The effects of Ag@Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The WVP decreased from 5.84 ± 0.71 × 10 −8 g/m 2 × kPa × h for uncoated paper to 0.17 ± 0.68 × 10 −8 –0.20 ± 0.31 × 10 −8 g/m 2 × kPa × h for coated paper. Srichiangsa et al [ 58 ] suggested that the coating of paper could reduce the number and size of pores on the paper surface, resulting in the poor permeability of the paper package to water vapor. Furthermore, the presence of nanoparticles in coated paper could reduce WVP by the formation of a tortuous path for water vapor transmission.…”
Section: Resultsmentioning
confidence: 99%
“…The WVP decreased from 5.84 ± 0.71 × 10 −8 g/m 2 × kPa × h for uncoated paper to 0.17 ± 0.68 × 10 −8 –0.20 ± 0.31 × 10 −8 g/m 2 × kPa × h for coated paper. Srichiangsa et al [ 58 ] suggested that the coating of paper could reduce the number and size of pores on the paper surface, resulting in the poor permeability of the paper package to water vapor. Furthermore, the presence of nanoparticles in coated paper could reduce WVP by the formation of a tortuous path for water vapor transmission.…”
Section: Resultsmentioning
confidence: 99%
“…Innovation related to the use of nanotechnology in food packaging and quality control is the focus in the modern food industry. The silver nanoparticles can be relatively uniformly distributed in a matrix of other materials such as pulp, plastics, and others and thus be more effective at killing bacteria and fungi, either in stock preparation proses (Kraśniewska, Galus & Gniewosz, 2020) or as a coating (Gottesman et al, 2011;Srichiangsa et al, 2022;Tsai et al, 2017;Wang et al, 2014). Packaging materials with nanoparticles of silver or coated silver containing coatings allow creating effective and safe antimicrobial packaging.…”
mentioning
confidence: 99%